2022
DOI: 10.3390/biology11081211
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Phenotypic Variation of Blastocystis sp. ST3 from Urban and Orang Asli Population—An Influential Consideration during Sample Collection in Surveys

Abstract: Blastocystis sp. is a globally distributed protozoan parasite with uncertain pathogenicity. Phenotypic variation in Blastocystis sp. suggests its adaptation; however, the phenotypic features of Blastocystis sp. ST3 from a distinct source of isolation is unknown. Blastocystis sp. isolated from individuals in urban and orang asli (indigenous population in Selangor, Malaysia) settlements were studied for phenotypic characteristics such as growth profile, morphology, ultrastructure, and resistance to harsh conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…Our findings demonstrated that Blastocystis sp.-infected individuals, regardless of symptoms, had decreased alpha diversity and Pielou's evenness. As observed in our recent study, greater amoebic forms and surface fuzzy coat commonly seen in symptomatic isolates [35] suggest a greater interaction with bacteria in these isolates which could contribute to the alteration of microbiota. On the other hand, lower peak cell numbers in the growth profile of symptomatic isolates implicate potential inhibition from accompanying microbiota.…”
Section: Discussionsupporting
confidence: 79%
“…Our findings demonstrated that Blastocystis sp.-infected individuals, regardless of symptoms, had decreased alpha diversity and Pielou's evenness. As observed in our recent study, greater amoebic forms and surface fuzzy coat commonly seen in symptomatic isolates [35] suggest a greater interaction with bacteria in these isolates which could contribute to the alteration of microbiota. On the other hand, lower peak cell numbers in the growth profile of symptomatic isolates implicate potential inhibition from accompanying microbiota.…”
Section: Discussionsupporting
confidence: 79%
“…A recent study has demonstrated variation due to the source of isolation in a single subtype. This suggests the influence of the microenvironment on Blastocystis and its infection [ 105 ]. Hence, to understand the dynamics of Blastocystis infection and its association with pathogenesis, it is necessary to include subtype information in all future epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%